MASTERING THE PMI-RISK PMI-RMP MANAGEMENT PROFESSIONAL EXAM complete coverage of the pmi... -rmp exam content outline and specifications updat. - Nielsen, Klaus, 1972- (PRODUCTIVITY PRESS, 2022)
Risk Management Professionals seek to identify, analyze, and document the risks associated with a company's business operations, as well as monitor the effectiveness of risk management processes and implement needed changes. The PMI Risk Management Professional (PMI-RMP) certification not only highlights the ability to identify and assess project risks, mitigate threats, and capitalize on opportunities, but it also enhances and protects the needs of the organization. Gaining distinction as a PMI-RMP sets the Risk Management Professional apart from other professionals and brings credit to an organization. The exams from the Project Management Institute are not easy, so whether you are running a course as an instructor or studying by yourself, you need a good study guide to maximize time spent studying and one which enhances the chances of passing the exam. Test takers sitting for the exam need a study guide that suggests which study materials are best to read in preparation for the exam, presents exercises to enhance learning and understanding, and provides sample exam questions. Most study guides just explain the contents of the exam without providing the tools to maximize learning. Klaus Nielsen, an Authorized Training Partner with PMI, translates the PMI examination content outline for April 2022 into what people need to do and know in preparation and provides them with exercises and prep questions as a quick and easy check to ensure they are on the right path in preparation for taking the exam. This book helps maximize the chance of passing the exam.